STRATEGI PENGHIDUPAN BERKELANJUTAN PADA KOMUNITAS PENGOLAH IKAN DI MASA PANDEMI COVID 19 (Studi Kasus Di Kalurahan Poncosari, Kepanewon Srandakan, Bantul) - Agustina Setyaningrum; Agung Satriyo Nugroho (Jurnal Sosial Ekonomi Kelautan dan Perikanan, 2022)
The fish processing community in Kuwaru Beach experienced some production problems during the  Covid 19 pandemic. This study aims to identify livelihoods and community livelihood strategies during the pandemic. This research is qualitative. The data collected are secondary data and primary data. Primary data were taken through observation, in-depth interviews, and documentation. Secondary data was taken through a literature review. The results showed that the community had good physical capital. Social capital, human capital, and natural capital are in the moderate. Meanwhile, financial capital is relatively low. They have difficulty accessing capital and do not have the requirements. No migration strategy was found in livelihoods. They carry out extensification and intensification strategies to maintain production activities